2004
DOI: 10.1038/sj.bjc.6601744
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer mortality trends in two areas of the province of Florence, Italy, where screening programmes started in the 1970s and 1990s

Abstract: We compared breast cancer mortality rates in the period 1985 -2000 in two areas of the province of Florence, Italy, where breast cancer screening programmes started in the 1970s (early screening (ES) area) and in 1990s (late screening (LS) area). The overall age-standardised mortality decreased in the whole period by 40.9% in the ES area (Po0.001), and by 11.3% in the LS area (P ¼ 0.030). Significant decreases in the ES area were detected in groups aged 45 -54 years (61.1%; P ¼ 0.018) and 65 -74 years (44.7%; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…20 Reductions in mortality of up to 40% have also been reported in areas of the province of Florence (Italy), where screening started in the 1970s. 21 The screening programme in Navarre was implemented very rapidly. In two years, it covered the entire population, and over time participation rates of more than 85% have been achieved.…”
Section: Discussionmentioning
confidence: 99%
“…20 Reductions in mortality of up to 40% have also been reported in areas of the province of Florence (Italy), where screening started in the 1970s. 21 The screening programme in Navarre was implemented very rapidly. In two years, it covered the entire population, and over time participation rates of more than 85% have been achieved.…”
Section: Discussionmentioning
confidence: 99%
“…31,46,48,52 -55 Of the three studies comparing time periods within a single country, all had adequate follow-up, and the estimates of mortality reduction compared with a prescreening period ranged from 28% to 36%. 41,53,64 IBM studies Table 3 shows the design characteristics of the IBM studies. The outcomes were generally compatible when differences in methodology and local circumstances were taken into account.…”
Section: Trend Studiesmentioning
confidence: 99%
“…Case-control studies (n ¼ 41 Paci, Eur J Cancer (2002) 42 Puliti, Br J Cancer (2008) 43 Barchielli, Cancer Causes Control (2001) 44 Paci, Br J Cancer (2002) 45 The Netherlands 1989 50-74 Otten, Int J Cancer (2008) 46 Otto, Cancer Epidemiol Biomarkers Prev (2012) 47 Otto, Lancet (2003) 48 van Schoor, Br J Cancer (2011) 15 Paap, Cancer Causes Control (2010) 49 Broeders enrolled in the study only if the breast cancer diagnosis occurred in a certain time/age window (taking into account eligibility and opportunity to be screened) and the population is classified by screening or by invitation to screening. Thus, for example, breast cancer deaths in the 15 years after screening is initiated in one region, from tumours diagnosed in that 15-year period, may be compared with the corresponding deaths from tumours diagnosed in the same period in a region without screening.…”
Section: )mentioning
confidence: 99%
“…Several guidelines and different expert groups recommend mammography screening examinations (IARC, 2002) despite the contradicting opinions questioning the positive effect of the screening (Gotzsche and Olsen, 2000). Recent evaluations have shown that service screening may be even more effective than screening in population-based trials Paci et al, 2002;Gorini et al, 2004). Information of actual participation to screening, data of incident cancers and detailed information of tumour characteristics have provided more precise information of breast cancer prognosis in the screened and not-screened patients (Ernst et al, 2004).…”
mentioning
confidence: 99%
“…Information of actual participation to screening, data of incident cancers and detailed information of tumour characteristics have provided more precise information of breast cancer prognosis in the screened and not-screened patients (Ernst et al, 2004). Comparison of incident-based breast cancer mortality before and after beginning of screening has shown a significant mortality reduction (Tabar et al, 2003;Gorini et al, 2004).…”
mentioning
confidence: 99%